Anterior Commissure Involvement in Humanherpes Virus 6 Encephalitis. Issue 1 (23rd September 2014) - Fujii, Katsunori; Ikehara, Hajime; Nagasawa, Koo; Hishiki, Haruka; Uchikawa, Hideki; Shimojo, Naoki
The anterior commissure is an evolutionarily conserved nerve bundle that connects the right and left hemispheres, playing pivotal neurological roles in visual, linguistic, and olfactory functions. The authors herein describe a 16-month-old boy with high fever, lethargy, and recurrent seizures. Polymerase chain reaction (PCR) examination detected human herpesvirus 6 (HHV-6) in both the cerebrospinal fluid and the pharyngeal swabs, leading to the diagnosis of HHV-6 encephalitis. Brain magnetic resonance imaging (MRI) 4 days after disease onset distinctly revealed anterior commissure involvement on diffusion-weighted images and apparent diffusion coefficient maps, suggesting that this lesion was cytotoxic edema. After treatment with 30 mg/kg/d methylprednisolone for 3 days, the anterior commissure involvement on MRI was completely diminished. This is the first MRI report rarely showing anterior commissure involvement in encephalitis, suggesting that this lesion might be caused by direct invasion of HHV-6 or transient axonal swelling associated with inferior temporal lobe damage.